PENGARUH PROPORSI KOMISARIS INDEPENDEN, KOMITE AUDIT, UKURAN PERUSAHAAN, PROFITABILITAS, DAN SOLVABILITAS TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Perbankkan Yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Sri Rahayu; Hardi Hardi; Alfiati Idris (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aim of this study was to examine the effect of proportion of independent commisarisse, audit commite, size, profitability, and solvability on the audit report lag. Independent variables used in this study are proportion of independent commisarisse, audit commite, size, profitability, and solvability, while dependent variables in this study is the audit report lag. The populations used in this study are all of banking compenies listed on IDX 2012-2014 where the total sample is used by 18 companies. The sampling thecnique in which the number of observation obtained this study was 54 (18x3). The method of analysis of this study using multiple regression analysis with help of softwere SPSS version 20,00. This study used classic assumption test composed of normality test , heteroskedasity test, autocorrelation test, and multi collinearity test. While hypothesis test is down with t test. The results of this study indicate that all independent variables are proportion of independent commisarisse, audit commite, size, profitability, and solvability on the audit report lag on the level of significant (α) < 0,05. The coefficient of determination as big as 79,9 indicates that 79,9% of the variations that occur in the audit report lag is affected by proportion of independent commisarisse, audit commite, size, profitability, and solvability while the rest of 20,1% were affected by other variabel that were not performed in this study.Keywords: proportion of independent commisarisse, audit commite, size, profitability, solvability.